Accessibility, Cost, and Quality of an Online Regular Follow-Up Visit Service at an Internet Hospital in China: Mixed Methods Study - Kun Wang; Wenxin Zou; Yingsi Lai; Chun Hao; Ning Liu; Xiang Ling; Xiaohan Liu; Ting Liu; Xin Yang; Chenxi Zu; Shaolong Wu (JMIR Publications, 2024)
BackgroundTelemedicine provides remote health care services to overcome constraints of time and space in accessing medical care. Similarly, internet hospitals in China support and provide remote health care services. Due to the COVID-19 pandemic, there has been a proliferation of internet hospitals. Many new services, including online consultations and regular online follow-up visit services, can now be accessed via internet hospitals in China. However, the accessibility, cost, and quality advantages of regular online follow-up visit services remain unclear. ObjectiveThis study aimed to evaluate the accessibility, costs, and quality of an online regular follow-up visit service provided by an internet hospital in China. By analyzing the accessibility, costs, and quality of this service from the supply and demand sides, we can summarize the practical and theoretical experiences. MethodsA mixed methods study was conducted using clinical records from 18,473 patients receiving 39,239 online regular follow-up visit services at an internet hospital in 2021, as well as interviews with 7 physicians, 2 head nurses, and 3 administrative staff members. The quantitative analysis examined patient demographics, diagnoses, prescriptions, geographic distribution, physician characteristics, accessibility (travel time and costs), and service hours. The qualitative analysis elucidated physician perspectives on ensuring the quality of online health care. ResultsPatients were predominantly middle-aged men with chronic diseases like viral hepatitis who were located near the hospital. The vast majority were from Guangdong province where the hospital is based, especially concentrated in Guangzhou city. The online regular follow-up visit service reduced travel time by 1 hour to 9 hours and costs by ¥6 to ¥991 (US $0.86-$141.32) depending on proximity, with greater savings for patients farther from the hospital. Consultation times were roughly equivalent between online and in-person visits. Physicians provided most online services during lunch breaks (12 PM to 2 PM) or after work hours (7 PM to 11 PM), indicating increased workload. The top departments providing online regular follow-up visit services were Infectious Diseases, Rheumatology, and Dermatology. The most commonly prescribed medications aligned with the prevalent chronic diagnoses. To ensure quality, physicians conducted initial in-person consultations to fully evaluate patients before allowing online regular follow-up visits, during which they communicated with patients to assess conditions and determine if in-person care was warranted. They also periodically reminded patients to come in person for more comprehensive evaluations. However, they acknowledged online visits cannot fully replace face-to-face care. ConclusionsTelemedicine services such as online regular follow-up visit services provided by internet hospitals must strictly adhere to fundamental medical principles of diagnosis, prescription, and treatment. For patients with chronic diseases, online regular follow-up visit services improve accessibility and reduce cost but cannot fully replace in-person evaluations. Physicians leverage various strategies to ensure the quality of online care.